Some Local Fractional Hermite-Hadamard-Type and Ostrowski-Type Inequalities for Exponentially s-Preconvex Functions with Generalized Mittag-Leffler Kernel (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we introduced the concepts of local fractional integral and generalized Mittag-Leffler kernel. Based on these, we establishHermite-Hadamard integral inequalities and Ostrowski integral inequalitiesvia exponentially s-preconvex functions and s-preconvex functions with generalized Mittag-Leffler kernel.